IDENTITY POLITICS IN PROGRESS: A CRITICAL EXAMINATION OF SYAFII MAARIF’S IDEAS - Mukhijab; Madrah, Muna Yastuti; Meredian Alam (UIN Raden Mas Said Surakarta, 2024)
In Indonesia’s political landscape, there is a current tension between identity politics and populist ideologies. Identity politics is a broad term used to describe political movements and actions related to religious identities and institutions, particularly in an Islamic setting. However, it raises concern about how we will investigate identity politics as part of a contextual, constituent-based approach to politics. The current study investigates Syafii Maarif’s political views. By employing a social hermeneutic approach and interpretive methodologies, this thought is elaborated in this study. The investigation reveals three primary elements of identity politics based on Maarif’s analysis: 1) ethnicity, 2) religion, and 3) political ideology. According to Maarif, any political activity that has these three characteristics is intrinsically saturated with identity politics. As a result, Muslim politics are often limited and narrowly defined. To address this constraint, the findings of this study advocate the actualization of the notion of identity politics to make space for populist politics. While religion, ethnicity, and political ideology coexist, a populist approach is still relevant in Islamic politics, persuasion methods, and specific constituency-based political connections.